Impact of climate variability, drainage and land-cover changes on hemiboreal streamflow. Issue 15 (18th November 2017) - Apsīte, Elga; Nikodemus, Oļģerts; Brūmelis, Guntis; Lagzdiņš, Ainis; Elferts, Didzis; Rendenieks, Zigmārs; Klints, Līga
ABSTRACT: The aim of the study was to determine the effects of climate variability, agricultural land drainage and afforestation of agricultural land on river discharge. The study was conducted in the Vienziemīte stream basin (6 km 2 ), where discharge was monitored on a daily basis during the time period of 1946–2010. In the stream basin, natural afforestation of agricultural land began in the 1950s, and in the mid-1970s artificial drainage systems were installed in all agricultural land (70% of the total basin area). Climate variability and artificial drainage were the main factors observed to be affecting stream discharge. The changes were most evident in annual and seasonal mean, minimum and maximum streamflow. There was no effect of afforestation of agriculture land on stream discharge.